Caracterization of the HIV-AIDS descentralization office in centro Havana - Bárbara Elena Hernández Rodríguez (Fundación para el Desarrollo de la Enfermería, 2009)
It was carried out a descriptive, retrospective and longitudinal study of the medical records of 245 people who have been diagnosed as having HIV-aids and who have been treated at the municipal decentralization office of Centro Havana from January 2006 through June 2008. The study was aimed at making a characterization of the office. The statistical analysis consisted on the calculation of the absolute and relative frequencies of each of the variables under study, using the SPSS statistical package, version 11.5. The study revealed that the highest percentage of patients was between 20 to 39 years old, in both sexes, with a prevalence of people who have completed either secondary or pre-university education. 60 % are retired, 60. 4% live crammed and the majority of them live on houses in regular or bad conditions. 72,6% of the studied group has a homosexual orientation. Based on the HIV and aids classification, 149 were diagnosed as having HIV. The studied group of highest incidence was the one selected. 99% became infected via sexual transmission. The more frequent unhealthy habit was a sedentary lifestyle. The most frequently reported side effect of the three-therapy treatment was the hyperlipidemia. The most prevalent opportunist infectious disease was Pneumonia by Pneumocistis Carini. Depressive neurosis was the main diagnosis at the medical office, while the most prevalent non-transmissible chronic disease was hypertension. Fourteen patients have died; 1873 consultations and 674 home visits have been made. We recommend that a medical multidisciplinary team be put together at the HIV-AIDS office, and that a plan of action will be created to solve the detected problems.